Shamanic regalia in the far north - Anawalt, Patricia Rieff (Thames & Hudson, 2014)
Probes into the significance and meaning of shamanic practices in Northeast Siberia, Alaska and British Columbia, and also points up the intriguing differences in the ritual garb as generation after generation sought to influence events through the aid of spirits.